2001
DOI: 10.1901/jaba.2001.34-425
|View full text |Cite
|
Sign up to set email alerts
|

Social Stories, Written Text Cues, and Video Feedback: Effects on Social Communication of Children With Autism

Abstract: This study investigated the effects of written text and pictorial cuing with supplemental video feedback on the social communication of 5 students with autism and social deficits. Two peers without disabilities participated as social partners with each child with autism to form five triads. Treatment was implemented twice per week and consisted of 10 min of systematic instruction using visual stimuli, 10 min of social interaction, and 10 min of self-evaluation using video feedback. Results showed increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
177
1
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(209 citation statements)
references
References 33 publications
17
177
1
14
Order By: Relevance
“…Technology offers carers the possibility of personalising stories by facilitating the use of graphic images, animated characters, digital pictures, video clips and sound files which suit the individual"s developmental age, learning style, reading ability, attention span and special interests. Some researchers have used multimedia (Hagiwara & Smith Myles, 1999), visual cues (Thiemann & Goldstein, 2001;Lorimer et al, 2002;Delano & Snell, 2006;Soenksen & Alper, 2006), verbal cues (Thiemann & Goldstein, 2001;Soenksen & Alper, 2006), music (Brownell, 2002), and personal photographs (Agosta et al, 2004;Ivey et al, 2004) to illustrate social stories and found that it helped children to understand the meaning behind the text. work environment (Smith, 2001).…”
Section: 2mentioning
confidence: 99%
“…Technology offers carers the possibility of personalising stories by facilitating the use of graphic images, animated characters, digital pictures, video clips and sound files which suit the individual"s developmental age, learning style, reading ability, attention span and special interests. Some researchers have used multimedia (Hagiwara & Smith Myles, 1999), visual cues (Thiemann & Goldstein, 2001;Lorimer et al, 2002;Delano & Snell, 2006;Soenksen & Alper, 2006), verbal cues (Thiemann & Goldstein, 2001;Soenksen & Alper, 2006), music (Brownell, 2002), and personal photographs (Agosta et al, 2004;Ivey et al, 2004) to illustrate social stories and found that it helped children to understand the meaning behind the text. work environment (Smith, 2001).…”
Section: 2mentioning
confidence: 99%
“…A possible response to this problem is through the use of predetermined scripts. Pre-determined scripts teach children with ASD role-specific dialogue in socio-dramatic play situations (Causton-Theoharis, J., & Malmgren, 2005;Charlop-Christy & Kelso, 2003;Thiemann & Goldstein, 2001). Activities can be incorporated into the inclusive classroom in which the whole student population participates in dramatic role-playing activities.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
“…Activities can be incorporated into the inclusive classroom in which the whole student population participates in dramatic role-playing activities. Educators model role-appropriate behaviour and speech, and provide opportunities for verbal and social exchanges between children with ASD and those without (Charlop-Christy & Kelso, 2003;Thiemann & Goldstein, 2001). Research indicates that following pre-determined script teaching sessions, role-appropriate speech and play in play settings increases among children with ASD (Charlop-Christy & Kelso, 2003;Ganz, Kaylor, Bourgeois, & Hadden, 2008;Thiemann & Goldstein, 2001).…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…O conjunto desses estudos demonstrou que o instrumento, em suas três versões, possui as principais propriedades psicométricas de validade e fidedignidade requeridas a uma medida psicológica. Cabe destacar ainda que foram encontrados estudos de avaliação na literatura em que o SSRS foi aplicado a crianças com autismo (Thiemann & Goldstein, 2001), deficiência auditiva (Souza, 2008), deficiência visual (Ferreira, 2008), adolescentes com Síndrome de Asperger (Koning & Maguill-Evans, 2001), dentre outros diagnósticos.…”
unclassified